Scared saviors: Evidence that people high in attachment anxiety are more effective in alerting others to threat. - Ein-Dor, Tsachi; Tal, Orgad (European Journal of Social Psychology, 2012)
Attachment-related anxiety has repeatedly been associated with poorer adjustment in various social, emotional, and behavioral domains. Building on social defense theory, we examined a possible advantage of having some group members who score high in attachment anxiety - a heightened tendency to deliver a warning message without delay. We led participants to believe that they accidently activated a computer virus that erased an experimenter's computer. We then asked them to alert the department's computer technicians to the incident. On their way, they were presented with four decision points where they could choose either to delay their warning or to continue directly to the technicians' office. We found that anxious individuals were less willing to be delayed on their way to deliver a warning message. This result remained significant when attachment avoidance, extroversion, and neuroticism were statistically controlled. Results are discussed in relation to the possible adaptive functions of certain personality characteristics often viewed as undesirable. Copyright © 2012 John Wiley & Sons, Ltd.